PENGARUH KOMPETENSI APARATUR, PARTISIPASI MASYARAKAT, PEMANFAATAN TEKNOLOGI INFORMASI, KOMITMEN ORGANISASI PEMERINTAH DESA, TRANSPARANSI DAN SISTEM PENGENDALIAN INTERN TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA (Studi Empiris Di Desa Motung, Pardumuan Motung dan Parsaoran Sibisa) - Ratih S. Panjaitan; Arthur Simanjuntak; Yosephine N. Sembiring; Septony Benyamin Siahaan (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2022)
This study aims to determine the effect of apparatus competence, community participation, use of information technology, organizational commitment of village government, transparency and internal control systems on the accountability of Village Fund management in Motung, Pardomuan Motung and Parsaora n Sibisa Villages. This type of research is causal associative research with a qualitative approach. This research was conducted in Motung Village, Pardomuan Motung, Parsaoran Sibisa located in Ajibata District, Toba Regency, North Sumatra Province. The population and samples in this study were 31 people who were 10 officials each in Motung Village, 11 people in Pardomuan Motung Village, 10 Parsaoran Sibisa People. This study uses primary data obtained using a questionnaire. While the data analysis method used in this study is the method of multiple linear regression analysis carried out with the help of SPSS 25 software. The results in this study found that the utilization of information technology, transparency and internal control systems had a positive significant influence on village fund management accountability. While the competence of the apparatus, community participation and commitment of village government organizations, do not have a significant influence on the accountability of village fund management.